Clinical Study and Outcome of Polycystic Ovarian Syndrome - Patil, Gayatri Linganagouda; Hosanemati, Geeta; Patil, LS; V, Vijayanath; Patil, Venkatesh M; Surpur, Rajeshwari R (Nepal Journal of Obstetrics and Gynaecology, 2011)
Aims : Polycystic ovarian syndrome (PCOS) is one of the common Gynaecological condition of diverse etiology 30% of the infertile women have anovulation due to polycystic ovarian disease, 20-30% of them have hyperandrogenemia and hyperprolactenemia. Method : An explorative type of hospital based study of 102 patient, during a 2 year period (Oct. 2008 – Oct. 2010) was done. Of which 75 (73.52%) were married women and 27 (26.47%) were unmarried women with varied symptomatology. Results: 67.6% of patients were in the age group 21-30 years. Ovulation induction was done in all the infertile group, an ovulation induction rate of 88.40% was achieved and of these 21 (34.42%) conceived, others on follow up. Of the unmarried women, all of whom had menstrual irregularities along with obesity (51.85%) and hirsutism (48.14%), after treatment 66.66% had an improvement in their symptoms, other still on follow up. Conclusion: This study demonstrates the various presentations either single or in combination and their response to various medical and surgical management. There should be a relational approach to therapy; treatment of polycystic ovarian syndrome should be tailored according to the major symptoms of the patients. DOI: http://dx.doi.org/10.3126/njog.v6i1.5248 NJOG 2011; 6(1): 22-27